Original articleMorphological analysis of vascular density in ependymomas - Duda-Szymańska, Joanna; Papierz, Wielisław (Folia Neuropathologica, 2007)
Ependymomas generally show slow growth rate and are associated with a long clinical history. In some cases however the biology of these tumours is considered to be unpredictable on the basis of histologic criteria. Density of microvessels was shown to serve in various malignant neoplasms as a prognostic factor that correlates with increased risk of metastasis and overall free survival. Some data suggest that density of blood vessels may be of prognostic value also in patients with neuroepithelial tumours. The aim of this study was to determinate whether that observation can be applied to ependymomas. The materials included 51 ependymomas G2 and G3 according to the WHO classification. Vasculature was visualized immunohistochemically in paraffin-embedded sections of tumour samples with CD31 and FVIII antibody. Density of blood vessels was calculated using a computed image analyzing system. The data were statistically evaluated. The density of blood vessels in anaplastic (WHO G3) ependymomas was shown to be significantly higher than that in WHO G2 type of the tumour, while there was no statistical difference between subtypes of WHO G2 ependymomas. The results suggest a connection between density of vasculature and the degree of histological malignancy in gliomas of ependymal derivation.